Colonoscopy Completion Rates and Reasons for Incompletion - Aljarallah, Badr; Alshammari, Badr (International Journal of Health Sciences, 2012)
Objectives: Colonoscopy is one of the major procedures in gastroenterology. Since the procedure is operator dependant, Quality of each procedure is the main element of reliable outcome. One of the elements is the completion rate. Completion rate of endoscopy unit is a reliable measure to improve the quality of the procedure. Methodology: We here reviewed retrospectively our endoscopy database from the main tertiary hospital in Qassim province, central part of Saudi Arabia. The recommended completion based on several professional societies range from 90 â€“ 95 % completion rate according to the indication. We retrospectively reviewed our endoscopy database over the period from 2005 to 2008 in King Fahad Specialist Hospital. Results: Our adjusted completion rate was 85.3 %.Â The main reason of incompletion was poor preparation. Our completion rate was comparable throughout the study period. Conclusion: our completion rate is below recommended range. We think this result will stimulate the efforts to incorporate more quality measures in the endoscopy unit. Key Words: Colonoscopy, Qassim Region